Odpowiedzi

2009-10-11T13:24:56+02:00
-12x + y =1
4x + 1/3 y =1 /3
-12x+y=1
12x+y=3 metoda przeciwnych współczynników dodajemy
2y=4 //2
y=2 wstawiamy do drugiego
12x+2=3
12x=1 //12
x=1/12 (ułamek)
y=2
1 5 1
2009-10-11T13:25:44+02:00
-12x+y=1
4x+1/3y=1/*3

-12x+y=1
12x+y=3

2y=4/2
y=2

-12x+2=1
y=2

-12x=1-2
y=2

-12x=-1/:(-12)
y=2

x=1/12
y=2
1 5 1
2009-10-11T13:28:18+02:00
-12x + y =1
4x + 1/3 y =1

y=1 + 12x
4x + 1/3(1 + 12x)

y=1 + 12x
4x + 1/3 + 4x=1

y=1 + 12x
8x=1-1/3

y=1 + 12x
8x=2/3 /:8

y=1 + 12x
x=1/12

y=1 + 12(1/12)
x=1/12

y=2
x=1/12
1 5 1